Differences in breast and cervical cancer screening between West and East Germany: a secondary analysis of a german nationwide health survey - Lena Marie Großmann; Hendrik Napierala; Wolfram J. Herrmann (BMC, 2023)
Abstract Background Breast cancer and cervical cancer are among the most common cancers in women in Germany. Early detection examinations such as mammography and the cervical smear test (Pap-test) have been shown to contribute to the reduction in the mortality and/or incidence of these cancers and can be utilised free of charge by women in certain age groups as part of national screening programmes. Analyses show that the use of health services varies regionally, especially when comparing the federal states of the former German Democratic Republic (GDR, Eastern Germany) and the Federal Republic of Germany (FRG, Western Germany). This study investigated to what extent the utilisation of mammography examinations and Pap-tests by women differs in federal states of former GDR and FRG. Methods For this purpose, we analysed data from the nationwide health survey GEDA14/15 conducted by the Robert Koch Institute (RKI) in 2014 and 2015. We calculated weighted proportions and compared attendance between eastern and western German states by a Chi-Square-test. Additionally, we conducted regression analysis to adjust for socio-economic status, living environment and place of birth. Results 2,772 female participants aged 20-34 years were analysed for Pap-test attendance in the last two years and 4,323 female participants aged 50-69 years old were analysed for mammography screening attendance in the last two years. 50-69-year-old women in eastern German states were with 78.3% (95%-CI 75.3%, 81.2%) more likely to attend mammography screening than in western Germany with 73.4% (95%-CI 71.8%, 74.9%). Pap-test uptake was statistically significantly higher in the East of Germany with 83.3% (95%-CI 79.6%, 87.1%) compared to 77.5% (95%-CI 75.8%, 79.3%) in the West of Germany. This relationship was robust to adjusting for socio-economic status, living environment and place of birth. Conclusions Cultural influences and socialization in the GDR might explain the higher utilisation of these cancer screening examinations at least to some extent. This could have many reasons, for example a higher health awareness through education or a possible greater trust in medical structures and the associated higher compliance of women. These hypotheses should be further explored to increase the uptake of screening examinations by women in Germany.